Functional Outcomes of Olecranon Process Fracture Treatment Using the Tension Band Wiring Technique - Parvez, Mohsin; Kaushik, Nischay; Sharma, Akhilesh Kumar; Roshan, Reetesh (Student’s Journal of Health Research Africa, 2024)
Background Olecranon fractures (OF) are a common elbow injury, often necessitating surgical intervention to restore function and anatomy. The tension band wiring (TBW) technique is frequently employed due to its biomechanical efficiency and cost-effectiveness. However, complications such as hardware irritation and infection remain concerns, highlighting the need for ongoing evaluation of its outcomes. This study retrospectively assessed the functional outcomes and complications of the TBW technique for treating olecranon process fractures. Methods Thirty individuals treated with TBW for isolated OF were included. Data on demographics, fracture classification, complications, and functional outcomes were collected. Functional outcomes were evaluated using the Mayo Elbow Performance Score (MEPS) and range of motion (ROM). Statistical analysis was performed using SPSS version 21.0. Results The average age was 42.5 years, with 60% male. The majority had Mayo Type IIB fractures (70%). Complications were noted in 20% of patients, primarily hardware irritation (13.3%) and infection (6.7%). The mean MEPS score improved significantly from 55.2 ± 10.5 at baseline to 88.5 ± 7.8 at the final follow-up (p < 0.001). Flexion-extension ROM increased from 90° ± 15° to 135° ± 10° (p < 0.01), and pronation-supination ROM from 60° ± 10° to 85° ± 5° (p < 0.01). Eighty per cent of patients achieved excellent or good outcomes. Conclusion The TBW technique demonstrated favourable functional outcomes with significant MEPS scores and ROM improvements. Despite a 20% complication rate, the complications were manageable. These findings support the efficacy of TBW in olecranon fracture management. Recommendations Future studies should explore modifications to the TBW technique and alternative materials to reduce complications.